![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
( 1+2+3+4-1-2-3-4) * 1*2*...........*8*9
= 0 * 1*2*...........*8*9
= 0
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 2^7 . 9^3 / 6^5 . 8^2
= 2^7 . 3^9 / 2^5 . 3^5 . 2^6
= 2^-4 . 3^4
![](https://rs.olm.vn/images/avt/0.png?1311)
Đặt \(A=5+5^2+5^3+....+5^{199}+5^{200}\)
\(\Leftrightarrow5A=5\left(5+5^2+5^3+....+5^{199}+5^{200}\right)\)
\(\Leftrightarrow5A=5^2+5^3+5^4+....+5^{200}+5^{201}\)
\(\Leftrightarrow5A-A=\left(5^2+5^3+5^4+....+5^{200}+5^{201}\right)-\left(5+5^2+5^3+....+5^{199}+5^{200}\right)\)
\(\Leftrightarrow4A=5^{201}-5\)
\(\Leftrightarrow A=\frac{5^{201}-5}{4}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
- \(x\cdot2\frac{4}{9}=4\frac{2}{5}-1\frac{4}{7}\)
\(x\cdot\frac{22}{9}=\frac{22}{5}-\frac{11}{7}\)
\(x\cdot\frac{22}{9}=\frac{99}{35}\)
\(x=\frac{99}{35}:\frac{22}{9}\)
\(x=\frac{81}{70}\)
Vậy \(x=\frac{81}{70}\).
- \(x:10\frac{6}{5}=4\frac{6}{5}+9\frac{7}{5}\)
\(x:\frac{56}{5}=\frac{26}{5}+\frac{52}{5}\)
\(x:\frac{56}{5}=\frac{78}{5}\)
\(x=\frac{78}{5}\cdot\frac{56}{5}\)
\(x=\frac{4368}{25}\)
Vậy \(x=\frac{4368}{25}\).
- \(x:3\frac{10}{3}=9\frac{1}{9}-5\frac{1}{9}\)
\(x:\frac{19}{3}=4\)
\(x=4\cdot\frac{19}{3}\)
\(x=\frac{76}{3}\)
Vậy \(x=\frac{76}{3}\).
![](https://rs.olm.vn/images/avt/0.png?1311)
\(1,\\ x+\dfrac{1}{2}=-\dfrac{5}{3}\\ x=-\dfrac{5}{3}-\dfrac{1}{2}\\ x=-\dfrac{13}{6}\\ Vậyx=-\dfrac{13}{6}\)
\(2,\\ \dfrac{1}{3}-x=\dfrac{3}{5}\\ x=\dfrac{1}{3}-\dfrac{3}{5}\\ x=-\dfrac{4}{15}\\ Vậyx=-\dfrac{4}{15}\)
\(3,\\ 3-4+x=\dfrac{7}{2}\\ -1+x=\dfrac{7}{2}\\ x=\dfrac{7}{2}+1\\ x=\dfrac{9}{2}\\ Vậyx=\dfrac{9}{2}\)
\(4,\\ x-\dfrac{4}{3}=-\dfrac{7}{9}\\ x=-\dfrac{7}{9}+\dfrac{4}{3}\\ x=\dfrac{15}{27}\\ Vậyx=\dfrac{15}{27}\)
\(5,\\ x-\left(-\dfrac{7}{3}\right)=\dfrac{5}{6}\\ x=\dfrac{5}{6}-\dfrac{7}{3}\\ x=-\dfrac{27}{18}\\ Vậyx=-\dfrac{27}{18}\)
\(6,\\ x-\dfrac{1}{5}=\dfrac{9}{10}\\ x=\dfrac{9}{10}+\dfrac{1}{5}\\ x=\dfrac{11}{10}\\ Vậyx=\dfrac{11}{10}\)
\(7,\\ x+\dfrac{5}{12}=\dfrac{3}{8}\\ x=\dfrac{3}{8}-\dfrac{5}{12}\\ x=-\dfrac{1}{24}\\ Vậyx=-\dfrac{1}{24}\)
\(8,\\ x+\dfrac{5}{4}=\dfrac{7}{6}\\ x=\dfrac{7}{6}-\dfrac{5}{4}\\ x=-\dfrac{9}{24}\\ Vậyx=-\dfrac{9}{24}\)
\(9,\\ x-\dfrac{2}{7}=\dfrac{1}{35}\\ x=\dfrac{1}{35}+\dfrac{2}{7}\\ x=\dfrac{11}{35}\\ Vậyx=\dfrac{11}{35}\\ 10,\\ x-\dfrac{1}{5}=-\dfrac{7}{10}\\ x=-\dfrac{7}{10}+\dfrac{1}{5}\\ x=-\dfrac{1}{2}\\ Vậyx=-\dfrac{1}{2}\)
ahiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiii hãy ấn a
`3^2 . 4 + 6^2 : 9 - 2^3 . 5`
`=9.4+36:9-8.5`
`=36+36:9-8.5`
`=36+4-8.5`
`=36+4-40`
`=40-40`
`=0`
=9.4+36:9-8.5
=36+4-40
=40-40=0